IMPLEMENTASI KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENGELOLA HUBUNGAN SEKOLAH DAN MASYARAKAT: STUDI KASUS PADA SDN 3 LAPE KABUPATEN SUMBAWA - John Kenedi; Arbi Batulante; Fatmawati Fatmawati (Program Studi PGSD Universitas Flores, 2023)
The study is aimed to find out the implementation of the principal's managerial competence in managing school and community relations through the school development program at SDN 3 Lape, Sumbawa Regency. The results of the research can be used by the school, especially at SDN 3 Lape to maximize their existing programs by involving related parties. The research will also provide an overview to the local governments regarding the implementation of school and community relations management executed by school. The research uses a qualitative approach with a case study type. Data acquisition in this study are gathered by interview techniques, observation and documentation. Data analysis was carried out by: (1) data reduction, (2) data display, (3) drawing conclusions and verification. Meanwhile data validation is executed by using triangulation of sources and methods. The study showed : 1) Implementation of the principal of SDN 3 Lape’s abilities from the aspects of coordination, interaction and communication was shown by coordination with the school committee to run meetings on supportting school development programs, building a cultural stage. 2) The implementation of the principal's managerial competence in establishing school and community relations involving alumni on the development of school programs at SDN 3 Lape has not been fully organized. Similarly, the school principal’s competency in establishing partnerships with the business world has not been maximally conducted by the school, it is shown by no collaboration document in the form of a MoU.